NGHIÊN CỨU LÝ THUYẾT CƠ CHẾ PHẢN ỨNG CỦA NGUYÊN TỬ O (1D) VỚI METANOL - Minh Huệ, Nguyễn Thị; Thọ, Nguyễn Hữu; Lin, M. C.; Yuan-Pern, Lee (Vietnam Journal of Chemistry, 2012)
The mechanism for the reaction of the oxygen atom (O1D) with methanol (CH3OH) molecule is studied using computational quantum method, namely B3LYP/aug-cc-pvtz. The potential energy surface (PES) for this system shows that eight different products have been found. The interesting result is that all reaction routes for the (O1D) + CH3OH needed through pre-association C1 (CH3(O)OH) complex. The formation of the product H2O+H2C=O is the most favorable. Our study would be contributing to understand more about the reaction mechanisms of the oxygen atom with methanol and in fact this reaction is one of the important ones in the atmosphere and combustion chemistry.